Doping in covalently functionalized carbon nanotubes: A Raman scattering study. Issue 12 (29th November 2016) - Gordeev, Georgy; Setaro, Antonio; Glaeske, Mareen; Jürgensen, Sabrina; Reich, Stephanie
Abstract : We experimentally investigate the effect of the structural and optoelectronic changes carbon nanotubes undergo after covalent functionalization. The carboxylation process alters the crystalline structure and the optical response of the tubes. We analyzed the intensity of disorder modes in the Raman spectra to estimate the structural degradation of the sp 2 network. After functionalization the bands associated with the G and 2D mode shift to higher frequency, indicating a change of the Fermi level Δ E F ∼ −0.5 and −0.65 eV in semiconducting and metallic nanotubes. This is also corroborated by the broadening of the semiconducting and narrowing of the metallic G mode phonons. Analysis of the luminescence correlated with absorption spectroscopy suggests that only the large‐diameter tubes remain present after the functionalization procedure, whereas the small‐diameter ( d < 8.2 Å) ones get destroyed in the process. The spectral shifts of the E 11 transition energies indicate uniaxial strain of ( ϵ = 0.18%) in the semiconducting nanotubes due to functionalization.